2020
DOI: 10.4103/jos.jos_25_20
|View full text |Cite
|
Sign up to set email alerts
|

The use of decorative braces in Jeddah, Saudi Arabia

Abstract: OBJECTIVE: To assess the practice of using orthodontic brackets as tooth decorations among dental offices and patients in Jeddah, Saudi Arabia. MATERIALS AND METHODS: The study was a cross-sectional survey using 2 questionnaires. The first included 14 doctor questions where 300 dental offices in Jeddah, Saudi Arabia were contacted by phone. The second questionnaire included 22 patient questions where 50 patients who currently have or have had decorative braces answered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In the present study, rheological analyses indicate favorable viscosity values for surface delivery of particles [26][27][28] . The high viscosity would not be of great value for the application proposed in the present study, since this can originate from a high crosslinking rate of the polymeric complex, thus generating the entrapment of the particle inside, preventing its action on the surface 27,28 .…”
Section: Discussionsupporting
confidence: 54%
“…In the present study, rheological analyses indicate favorable viscosity values for surface delivery of particles [26][27][28] . The high viscosity would not be of great value for the application proposed in the present study, since this can originate from a high crosslinking rate of the polymeric complex, thus generating the entrapment of the particle inside, preventing its action on the surface 27,28 .…”
Section: Discussionsupporting
confidence: 54%
“…Similarly, DIY braces or decorative braces in Saudi Arabia and the Philippines involve the sale of kits for self-fitting with 'over-the-counter' glue. 17,18 In Malaysia, fake braces differ in that the provider physically attempts dental treatment on clients, potentially violating the Dental Act 2018 19 or by practising dentistry in an unlicensed premise under the Private Healthcare Facilities and Services Act 1998. 20 Successful convictions demand meticulous evidence collection.…”
Section: Discussionmentioning
confidence: 99%
“…A crosssectional study found that the use of fake braces is affected by factors such as perceived susceptibility, family socioeconomic status, and risk severity [7]. 36.4% of dental offices in Jeddah, Saudi Arabia, offer decorative braces [8]. Additionally, 74% of fake braces are installed by patients or their friends and family using over the counter glue [8].…”
Section: Introductionmentioning
confidence: 99%
“…36.4% of dental offices in Jeddah, Saudi Arabia, offer decorative braces [8]. Additionally, 74% of fake braces are installed by patients or their friends and family using over the counter glue [8].…”
Section: Introductionmentioning
confidence: 99%